Analysis of playing styles according to team quality and match location in Greek professional soccer - Gómez, M.-A.; Mitrotasios, M.; Armatas, V.; Lago-Peñas, C. (International Journal of Performance Analysis in Sport, 2018)
The aim of the current study was to identify the styles of play of Greek Superleague soccer teams according to match location and team`s ranking using performance indicators related to attack, defence, transition and set-pieces. Data were obtained from the 2013-2014 season (n = 301 matches). The factor analysis identified eight factors (explained 64.29% of the total variance): F1 (ball possession); F2 (ending actions); F3 (individual challenges); F4 (counter-attack); F5 (set-piece); F6 (transitional-play); F7 (fouling actions); and F8 (free-kick). The results of the ANCOVA showed that home and away performances were significant different for F1, F2, F5, F6, and F7 with better values for home teams. In addition, the results of the covariate effect (team`s ranking) showed that the F1, F2 and F3 were significant reflecting an effect of ranking on these Factors when differentiating home and away teams (teams ranked 1st to 6th positions obtained greater values for F1 and F2, and less values for F3 than teams ranked 7th to 12th and 13th to 18th. The measures of tactics and strategies showed specific trends by ranking and match location that should be taken into account by coaches and performance analysts when identifying specific styles of play in soccer.